How can clinical ethics guide the management of comorbidities in the child with Rett syndrome? - Downs, Jennepher; Forbes, D.; Johnson, M.; Leonard, H. (Wiley-Blackwell Publishing Ltd., 2016)
Rett syndrome is a rare disorder caused by a mutation in the MECP2 gene. Those affected generally have severe functional impairments, and medical comorbidities such as scoliosis and poor growth are common. There is a paucity of information on the natural history of many rare disorders and an even greater deficit of evidence to guide best practice. The population-based and longitudinal Australian Rett Syndrome Database established in 1993 has supported investigations of the natural history of Rett syndrome and effectiveness of treatments. This paper reviews the disorder Rett syndrome and evidence for the management of scoliosis and poor growth within a clinical ethics framework. Compared with conservative management, we have shown that spinal fusion is associated with reduced mortality and better respiratory health. We have also shown that gastrostomy insertion is associated with subsequent weight gain. Family counselling for both procedures necessarily must include family perspectives and careful clinical attention to their needs and wishes. Vignettes describing family decision-making and experiences are presented to illustrate the principals of beneficence and autonomy in determining the best interests of the child and family. A blend of evidence-based practice with a strong clinical ethics framework has capacity to build existing strengths in families and reduce the negative impacts of disability and in so doing, optimise the health and wellbeing of those with Rett syndrome.